Enhancement of Titania Photoanode Performance by Sandwiching Copper between Two Titania Layers - Fan Yang (Materials, 2020)
Vacancies in semiconductors can play a versatile role in boosting their photocatalytic activity. In this work, a novel TiO2/Cu/TiO2 sandwich structure is designed and constructed. Abundant vacancies were introduced in TiO2 lattice by Cu reduction under heat treatment. Meanwhile, Cu atom could diffuse into TiO2 to form Cu-doped TiO2. The synergistic effect between oxygen vacancies and Cu atoms achieved about 2.4 times improved photocurrent of TiO2/Cu/TiO2 sandwich structure compared to bare TiO2 thin film. The enhanced photoactivity may be attributed to regulated electron structure of TiO2 by oxygen vacancies and Cu dopant from experimental results and density functional theory calculations. Oxygen vacancies and Cu dopant in TiO2 formed through copper metal reduction can introduce impurity levels and narrow the band gap of TiO2, thus improve the visible light response. More importantly, the Cu2+ and oxygen vacancies in TiO2 lattice can dramatically increase the charge density around conduction band and promote separation of photo-induced charge carriers. Furthermore, the oxygen vacancies on the surface may serve as active site for sufficient chemical reaction. This work presents a novel method to prepare doped metal oxides catalysts with abundant vacancies for improving photocatalytic activity.